'Touch' Your Heritage: An Interactive Installation on Multilingual Identity. Issue 1 (March 2015) - Ng, Bee Chin; Cheryl, Tan Xue Er; Cavallaro, Francesco; Gottlieb, Halina
Using an online and touch screen interface, this paper explores language and cultural identity as a form of intangible heritage. The relationship between language and cultural identity has spawned several studies in various disciplines in the past few decades. This study represents a first attempt at visualising some of the issues relevant to cultural identity discussed by linguists, psychologists and cultural studies experts in an interdisciplinary collaboration between linguists and digital design heritage researchers and computer programmers. For the purpose of this study, an interactive program that centres on the issue of cultural identity, heritage and language was developed to engage participants. Via a touch screen, several prompts and triggers related to culture, identity and heritage were embedded for participants to choose. The engagement includes allowing the participants to emphasize one identity trait over another as well as minimising the less relevant traits. Participants explore their perception of others and themselves via touching and manipulating the onscreen text. These participants were asked to fill in a questionnaire that was designed to elicit their thoughts about the program and on the relationship between cultural identity and language. The findings indicate that the participants considered language to be a crucial element of their identity and heritage though the different ethnic groups attributed different reasons for this response. It affirmed the "Touch my heritage" multilingual identity programme as a successful way to engage participants to think about complex and abstract issues such as culture and identity.